Surface Plasmon Resonance Assay for Label‐Free and Selective Detection of Xylella Fastidiosa. Issue 10 (8th October 2021) - Sarcina, Lucia; Macchia, Eleonora; Loconsole, Giuliana; D'Attoma, Giusy; Saldarelli, Pasquale; Elicio, Vito; Palazzo, Gerardo; Torsi, Luisa
Abstract : Biosensors In article number 2100043 by Luisa Torsi and co‐workers, screening of X. fastidiosa plant pathogen is performed by Surface Plasmon Resonance. The study proves the bacterium direct‐assay on a cm‐sized gold surface, modified with antibodies covalently bound to the detecting interface. Unprecedent selectivity is shown, and the affinity constant of the X. fastidiosa immunoassay is determined as well.